ХАЛЫҚ ПЕДАГОГИКАСЫНДА ЖАСЛАРҒА ӘДИРАСПАН ӨСИМЛИГИНИҢ ЕМЛИК ҚӘСИЙЕТИН ҮЙРЕТИЎ ДӘСТҮРЛЕРИ - Курбанбаева, А.Ж. (FAN va JAMIYAT, 2020)
The article contains thorough information about medicinal properties of plant-Peganum harmala that has been used in folk medicine for a long time Harmola is widely used for treating different diseases.